Effects of Blidingia sp. Extract on Intestinal Inflammation and Microbiota Composition in LPS-Challenged Mice - Song, Wei; Li, Yan; Zhang, Xuelei; Wang, Zongling (Frontiers in Physiology, 2019)
Blidingia sp. is a green alga that has spread rapidly in Subei Shoal, China. To explore the potential beneficial effects of Blidingia sp., we investigated the anti-inflammatory activity of its water–methanol extract of Blidingia sp. in a mouse model of lipopolysaccharide (LPS)-induced intestinal inflammation. The results revealed that the administration of Blidingia extract significantly alleviated the LPS-induced increase of the inflammatory cytokine content in the serum, as well as latter’s gene expression in the ileum. Moreover, the extract inhibited the phosphorylation of NF-κB and IκBα in LPS-challenged mice. Apart from these changes, the extract also averted intestinal morphology damage(s) and cell apoptosis in mice. Interestingly, the extract also had beneficial effects on the diversity and composition of caecal microbiota in LPS-challenged mice. In conclusion, the results suggested that Blidingia extract had beneficial effects on the recovery of intestinal function by reducing the inflammatory response, improving the maintenance of intestinal morphology, and decreasing cell apoptosis in LPS-induced intestinal inflammation. In addition, the beneficial effects of the extract on caecal microbiota composition may play a role in its anti-inflammatory activity. These results suggested that Blidingia extract could be potentially used in preventing intestinal inflammation.